The law and practice of banking : volume 1: banker and customer - Holden, J. Milnes (London : Pitman Publishing, 1991)
This fifth edition of Volume 1 draws attention to recent developments in the law and practice of banking. It takes account of new statutes affecting bankers, in particular the financial services act of 1986, etc.
Includes index.
rua 10/03/2015, ijb 03/04/2019
Loans
Keywords: Banking law; Banks and banking; Banks and customers; Great Britain